2018
DOI: 10.3390/rs10111692
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Multi-Source Evapotranspiration Products over China Using Eddy Covariance Observations

Abstract: As an essential variable in linking water, carbon, and energy cycles, evapotranspiration (ET) is difficult to measure. Remote sensing, reanalysis, and land surface model-based ET products offer comprehensive alternatives at different spatio-temporal intervals, but their performance varies. In this study, we selected four popular ET global products: The Global Land Evaporation Amsterdam Model version 3.0a (GLEAM3.0a), the Modern Era Retrospective-Analysis for Research and Applications-Land (MERRA-Land) project,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 142 publications
0
26
0
Order By: Relevance
“…(Wei et al, 2017). Other observational studies suggest that annual T / ET averages nearly 2/3 globally (0.61 ± 0.15, Schlesinger and Jasechko, 2014;0.64 ± 0.13, Good et al, 2015; and 0.66 ± 0.13 across some FLUXNET sites, Li et al, 2019). Intercomparison studies agree on the large uncertainty surrounding these estimates, with reported global terrestrial annual T / ET ratios ranging from 0.35 to 0.90 (Coenders-Gerrits et al, 2014;Fatichi and Pappas, 2017;Young-Robertson et al, 2018).…”
Section: Vegetation Plays a Central Role In Evaporation And Transpiramentioning
confidence: 90%
See 4 more Smart Citations
“…(Wei et al, 2017). Other observational studies suggest that annual T / ET averages nearly 2/3 globally (0.61 ± 0.15, Schlesinger and Jasechko, 2014;0.64 ± 0.13, Good et al, 2015; and 0.66 ± 0.13 across some FLUXNET sites, Li et al, 2019). Intercomparison studies agree on the large uncertainty surrounding these estimates, with reported global terrestrial annual T / ET ratios ranging from 0.35 to 0.90 (Coenders-Gerrits et al, 2014;Fatichi and Pappas, 2017;Young-Robertson et al, 2018).…”
Section: Vegetation Plays a Central Role In Evaporation And Transpiramentioning
confidence: 90%
“…The ratio of transpiration to evapotranspiration (T / ET) at annual timescales is related to aridity (Good et al, 2017) but appears to be relatively insensitive to annual precipitation (P ) (Schlesinger and Jasechko, 2014). T / ET is sensitive to ecosystem characteristics, namely the leaf area index (LAI) Fatichi and Pappas, 2017;Wang et al, 2014;Wei et al, 2015), especially on sub-annual timescales (Li et al, 2019;Scott and Biederman, 2017), noting that LAI is related to P at longer timescales. A higher LAI favors T and E from intercepted water (E i ) at the expense of E from soil (E soil ) such that LAI explains some 43 % of the variability of annual T / ET across global ecosystems .…”
Section: Vegetation Plays a Central Role In Evaporation And Transpiramentioning
confidence: 99%
See 3 more Smart Citations